MORPHOFUNCTIONAL CHARACTERISTICS OF THE HYMEN IN GIRLS IN THE AGE CATEGORIES OF SECOND CHILDHOOD IN THE UZBEK POPULATION - Kurmasheva , J; Indiaminov , S; Yunusova , N (Uzbekistan Open Conference, 2025)
In girls in the second childhood age group (8–11 years), the hymen was characterized by annular, oval, round-oval, and crescent-shaped shapes with a slightly stretchable consistency. The average hymenal parameters in girls in the Uzbek population during the first childhood were: hymenal wall height 0.4 (medium height), wall thickness 0.1 (thin), and hymenal opening size 1.0 (small). In girls in the second childhood age group, these parameters were: hymenal wall height 0.4 (medium height), wall thickness 0.2 (thin), and natural opening size 1.15 (medium).
Keywords: girls; in the Uzbek population; second childhood; hymen; morphofunctional condition; metric parameters; diagnostics; significance; expert assessment